Implementasi Keputusan Direktur Jenderal Bimbingan Masyarakat Islam Nomor 189 Tahun 2021: Perspektif Tipologi KUA di Kabupaten Kutai Timur - Subagyo, Edy; Iswanto, Bambang; Rahmi Hs, Maisyarah (Medina-te : Jurnal Studi Islam, 2023)
The Ministry of Religion in East Kutai District conducts pre-marital marriage counseling for prospective brides and grooms, organized by the sub-district Religious Affairs Offices (KUA). These KUA offices are classified into different typologies, namely C, D1, and D2, based on rules and regulations established by the Ministry of Religion. Factors taken into consideration for this classification include geographic conditions and the number of marriage events. These typological differences give rise to unique challenges and issues. In this context, the research problem is formulated: How is the implementation of Director General of Islamic Guidance (Kepdirjen Bimas Islam) Regulation Number 189 of 2021 concerning the execution of pre-marital marriage counseling for prospective brides and grooms in East Kutai District?. The research methodology employed is qualitative, specifically a Field Research approach with sociological-legal orientation. Data is collected through observation, interviews, and documentation, followed by data condensation, presentation, conclusion drawing, and data validity techniques for data analysis. The results indicate variations in the implementation of Kepdirjen Regulation Number 189 of 2021 in different KUA typologies. KUA typology C utilizes face-to-face or group methods, while typology D1 and D2 employ independent methods for pre-marital counseling. This divergence is attributed to the challenging geographic conditions of typologies D1 and D2, where these methods are deemed suitable and effective. Additionally, the hindrances and support mechanisms in the implementation of pre-marital counseling are linked to the limited infrastructure in typologies D1 and D2, particularly concerning electrical and network accessibility, which hampers service provision in these regions.